2012
DOI: 10.1111/j.1570-7458.2012.01311.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation of fruit color, elongation, hardness, and volume to the infestation of olive cultivars by the olive fruit fly,Bactrocera oleae

Abstract: The susceptibility of olive cultivars to the olive fruit fly, Bactrocera oleae (Rossi) (Diptera: Tephritidae),\ud has seldom been studied. This article examines factors associated with olive fruit fly infestation\ud of 16 commonly planted Sicilian olive cultivars. Total infestation data were simultaneously correlated\ud with categorical and quantitative factors using ordinal logistic regression. When all factors were\ud included in the analysis, year, sampling date, cultivar, and fruit color were highly signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 18 publications
(31 reference statements)
4
39
0
Order By: Relevance
“…Our hypothesis is that volatiles emitted by olive leaves may interfere in olive fly females' host selection in conjunction with olives (Malheiro et al, 2015b) and with other factors, such as physical (fruit and leaf color, shape, volume) (Rizzo et al, 2012) and biochemical aspects (olives maturation) (Gonçalves et al, 2012). In fact, when host volatiles from olive leaves and fruits were tested in electroantenographic studies in olive fly males and females (mated and unmated), higher EAG signals were obtained with olive leaf volatiles, especially in mated males (Liscia et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our hypothesis is that volatiles emitted by olive leaves may interfere in olive fly females' host selection in conjunction with olives (Malheiro et al, 2015b) and with other factors, such as physical (fruit and leaf color, shape, volume) (Rizzo et al, 2012) and biochemical aspects (olives maturation) (Gonçalves et al, 2012). In fact, when host volatiles from olive leaves and fruits were tested in electroantenographic studies in olive fly males and females (mated and unmated), higher EAG signals were obtained with olive leaf volatiles, especially in mated males (Liscia et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The female of this dipteran shows cultivar preference by attacking specific olive cultivars (Burrack and Zalom, 2008;Iannotta et al, 2007;Navrozidis et al, 2007;Gonçalves et al, 2012). Host selection for oviposition is believed to be based on chemical (Imperato et al, 2012;Kombargi et al, 1998;Spadafora et al, 2008), physical (Neuenschwander et al, 1985;Rizzo et al, 2012), and molecular aspects . More recently, increasing evidence has been found that microbiological factors are also important in the oviposition preference of the olive fly.…”
Section: Introductionmentioning
confidence: 99%
“…In further study, Rizzo et al. () found that quantitative factors such as olive fruit size, shape and colour are significant only if the variety factor is eliminated. It has even been hypothesized that B. oleae females are able to select fruits that are better adapted for the development of their progeny (e.g., larval developmental time, pupal emergence time and pupal weight; Burrack & Zalom, ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between olive fruit size and B. oleae oviposition preferences is a controversial issue. Research exists that indicates that these measures both correlate (Gümusay et al, 1990;Neuenschwander et al, 2009;Rizzo et al, 2012) and do not correlate (Iannotta, Perri, Tocci, & Zaffina, 1999). It has even been proposed that olive fruit size is the most important parameter during the early stages of fruit ripening but, subsequently, it becomes less important due to both the increase in the population density and the presence of particular substances in the olives that induce females to select the smaller drupes for ovipositing (Dominici, Pucci, & Montanan, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation